2012
DOI: 10.1590/s0102-05362012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Yield and shelf life of chrysanthemum in response to the silicon application

Abstract: The potted chrysanthemum is one of the main flowers produced in protected cultivation. Silicon has promoted improvements both in quantitative and qualitative aspects when supplied to some ornamental species produced in these conditions. We evaluated the response of chrysanthemum cultivars grown in pots to the application of silicon. The experiment was conducted in a greenhouse of the Universidade Federal de Viçosa, Minas Gerais state, Brazil. Treatments were arranged in a 3x2 factorial scheme (three cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…The most recent studies examining the role of Si have been performed in flowers with post-harvest and production, such as calla (Almeida et al 2009), rose (Locarno et al 2011), gerbera (Guerrero et al 2012), chrysanthemum (Carvalho-Zanao et al 2012, Sivanesan et al 2013) and ornamental sunflower , Oliveira et al 2013). The only work examining the role of Si in ornamental plants grown in vitro has been performed in orchids , Soares et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent studies examining the role of Si have been performed in flowers with post-harvest and production, such as calla (Almeida et al 2009), rose (Locarno et al 2011), gerbera (Guerrero et al 2012), chrysanthemum (Carvalho-Zanao et al 2012, Sivanesan et al 2013) and ornamental sunflower , Oliveira et al 2013). The only work examining the role of Si in ornamental plants grown in vitro has been performed in orchids , Soares et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The response to Si supplementation mainly depends on the amount of Si the plant takes up and the amount of Si that is available in the substrate. Carvalho-Zanão et al (2012) did not observe any significant response of chrysanthemum to supplemental Si. Mattson & Leatherwood (2010), evaluating 21 species of flowers, found that, among these species, begonia, petunia, geranium, impatiens and vinca did not present any significant morphological response to the application of Si.…”
Section: Traitmentioning
confidence: 60%
“…There were differences of Si uptake among cultivars: 'White Friendship' demonstrated the highest concentration (0.45 g kg -1 ), followed by 'Rose Friendship' (0.38 g kg -1 ) and 'Red Beauty' (0.37 g kg -1 ) ( Table 3). Carvalho-Zanão et al (2012) also observed genotypic differences regarding the uptake of Si in chrysanthemum and Zanão Júnior et al 2013in roses. According to Epstein (1999), Si concentrations in plants generally range 0.1-100 g kg -1 and, in plants known as Si accumulators, such as rice, it may be higher than that of macronutrients (> 100 g kg -1 ).…”
Section: Traitmentioning
confidence: 77%
“…Roses with Si added to the nutrient formula also showed a decrease in leaf and flower senescence [11]. The shelf life of Chrysanthemum L. cut flowers was also extended [12]. Hydroponically-produced gerbera plants supplemented with Si had improved overall crop and flower quality [13].…”
Section: Introductionmentioning
confidence: 99%